An Analysis of Simile in War Room Movie - Yosua Timotius Natanael; Gina Indriani; Muhammad Ridho Fajar Nugraha; Nurma Dhona Handayani (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The aim of this research is to analyze simile and its type in the movie “War Room” (2015) directed by Alex Kendrick. Similes are employed in a number of ways and serve a range of purposes, including movie. Therefore, this study applied qualitative research as the design and focused on analyzing simile, which is part of semantics study. A simile is a clear comparison, and it frequently uses comparative terms like or as. The type of similes is categorized by Dancygier & Sweetser (2014) into narrow-scope and wider-scope similes. As the result of the research, there were 20 similes found in the movie, such as 4 similes using “as” and 16 similes using ‘like’ as the comparison word. Moreover, there were 11 narrow-scope similes and 9 wider-scope similes apparent in the movie’s narration and conversation.